Identifikasi Permasalahan Kecemasan Sosial dan Penanganannya Pada Remaja di Panti Asuhan - Widya Kartika Sari; Nurul Jannah; Vira Afriyanti (Bulletin of Counseling and Psychotherapy, 2022)
Social anxiety is one of the barriers for children to interact in the social environment. The purpose of this study was to identify the level of social anxiety of adolescents (orphanage/fosterage children) and to reveal how the care provided by the orphanage coaches towards social anxiety problems. This research is a quantitative descriptive study with a sample of fifty people from three orphanages. The data collection technique in this study used a social anxiety instrument with a Likert scale and analyzed using a frequency distribution. The findings in this study identified a very high level of adolescent social anxiety 28%. , 54% high, and 18% moderate for the average level of anxiety in the high category, while the handling process carried out by the foster caretaker on average was done by providing advice, motivation and guidance to the fostered orphanage children to be able to interact properly and confidently but not yet structured so that programmed guidance and counseling services are needed to control the level of social anxiety so as to be able to develop social interaction skills optimally.